Blood flow restricted walking alters gait kinematics - Walden, T. P.; Fairchild, T.; Girard, O.; Peiffer, J. J.; Jonson, A. M.; Dempsey, A. R. (European Journal of Sport Science, 2023)
This study investigated the impact of blood flow restriction (BFR) during treadmill walking on gait kinematics. Twenty-one participants completed one familiarisation and four experimental sessions, including two walking speeds (moderate [5.0 ± 0.3km·h-1] and fast [6.4 ± 0.4km·h-1]) and two occlusion conditions (BFR [60% of arterial occlusion pressure] and unrestricted). For each exercise intensity, the BFR session was performed first. Participants were instructed to walk as long as possible, with sessions capped at 20 min. Unrestricted sessions were time-matched, and the order of exercise intensity was randomised. Kinematics were collected over 10s every minute using retro-reflective markers affixed to specific body landmarks. Ratings of perceived exertion and discomfort were collected every two minutes. Blood samples were collected from the fingertip pre-exercise and the finger and toe post-exercise, and were analysed for lactate, electrolytes, and markers of cell-membrane damage. During the BFR sessions the cuffs remained inflated while the blood samples were collected. Fast-walk BFR sessions exhibited higher anterior trunk flexion (p = 0.001) and knee flexion during stance (p = 0.001) compared to all other sessions. Step width was increased during BFR sessions (p = 0.001), but no difference in step length (p = 0.300) or cadence (p = 0.922) were observed. The time required to elicit change in anterior trunk flexion and plantar-flexion angle at toe-off was shorter during BFR sessions (p = 0.024). The BFR sessions elicited the highest ratings of perceived exertion and discomfort, as well as blood lactate concentration (p = 0.001). Application of BFR during moderate and fast treadmill walking modifies gait kinematics and exacerbates exercise-related sensations as well as blood lactate concentration.